Virtual Planning of a Complex Three-Part Bimaxillary Osteotomy - Chiara Di Blasio; Marilena Laura Anghinoni; Alberto Di Blasio (Case Reports in Dentistry)
In maxillofacial surgery, every patient presents special problems requiring careful evaluation. Conventional methods to study the deformities are still reliable, but the advent of tridimensional (3D) imaging, especially computed tomography (CT) scan and laser scanning of casts, created the opportunity to better understanding the skeletal support and the soft tissue structures. Nowadays, virtual technologies are increasingly employed in maxillofacial surgery and demonstrated precision and reliability. However, in complex surgical procedures, these new technologies are still controversial. Especially in the less frequent cases of three-part maxillary surgery, the experience is limited, and scientific literature cannot give a clear support. This paper presents the case of a young patient affected by a complex long face dentofacial deformity treated by a bimaxillary surgery with three-part segmentation of the maxilla. The operator performed the surgical study completely with a virtual workflow. Pre- and postoperative CT scan and optical scanning of plaster models were collected and compared. Every postoperatory maxillary piece was superimposed with the presurgical one, and the differences were examined in a color-coded map. Only mild differences were found near the osteotomy lines, when the bony surface and the teeth demonstrated an excellent coincidence.